The Issue of Nullifying a Judgment in Criminal Procedural Law - Gökhan Ölmez (İstanbul Hukuk Mecmuası)
This study examines whether a judgment given by courts functionally empowered to conduct criminal proceedings can be legally nullified. As a judicial proceeding, judgment appears in legal world through occurrence of material, voluntary and formal conditions. Whether a judgment given by criminal court may be acceptably deemed null due to the nature of defect it contains and therefore be incapable of having any legal consequences is an important issue to explain in terms of judicial proceedings theory. In case of nullification of a judgment given by an empowered court, apart from that judgment’s unlawfulness by qualification of illegality, other questions are also to be answered, such as the criteria by which this qualification is made and which persons or authorities are authorized to make this classification by criminal procedural system adopting the audit of legal remedy. This study will exhibit opinions for and against the nullification of a judgment by emphasizing practical importance of the subject and identify whether the nullification of a criminal court judgment is acceptable within the framework theory of judicial proceedings prevalent in criminal procedural law.In this context, this study will provide explanations about practices developed by German Federal and State Courts based on their decisions about nullifying a judgment. Lastly, study will examine judgments indicative of a nullification in Turkish criminal procedural law and discuss whether the practice of distinctly subjecting a judgment to nullification is accurate or not without regard to the general legal remedial system ensured in Turkish Criminal Procedural Code.